Estimating the contribution of organic acids to northern hemispheric continental organic aerosol. Issue 14 (23rd July 2015) - Yatavelli, Reddy L. N.; Mohr, Claudia; Stark, Harald; Day, Douglas A.; Thompson, Samantha L.; Lopez‐Hilfiker, Felipe D.; Campuzano‐Jost, Pedro; Palm, Brett B.; Vogel, Alexander L.; Hoffmann, Thorsten; Heikkinen, Liine; Äijälä, Mikko; et al.
Abstract Using chemical ionization mass spectrometry to detect particle‐phase acids and aerosol mass spectrometry (AMS) measurements from Colorado, USA, and two studies in Hyytiälä, Finland, we quantify the fraction of organic aerosol (OA) mass that is composed of molecules with acid functional groups (facid). Molecules containing one or more carboxylic acid functionality contributed approximately 29% (45–51%) of the OA mass in Colorado (Finland). Organic acid mass concentration correlates well with AMS m/z 44 (primarily CO2+), a commonly used marker for highly oxidized aerosol. Using the average empirical relationship between AMS m/z 44 and organic acids in these three studies, together with m/z 44 data from 29 continental northern hemispheric (NH) AMS data sets, we estimate that molecules containing carboxylic acid functionality constitute on average 28% (range 10–50%) of NH continental OA mass with typically higher values at rural/remote sites and during summer and lower values at urban sites and during winter.